Implementasi Manajemen SDM Terhadap Pengembangan Profesionalitas Tenaga Pendidik : di Madrasah Diniyyah Al-Amiriyyah Blokagung Banyuwangi Kolaborasi Antara Tenaga Kependidikan dengan PKM Kurikulum - Moch. Karim Amirudin; Moh. Harun Al-Rosyid (PT. ALHAFI BERKAH INDONESIA, 2024)
This research is based on data that shows that qualified human resources will enable educational institutions to achieve their goals easily. By applying good managerial concepts, it is hoped that competitively managed educational institutions can compete healthily and purposefully. This treatise was written with the aim of understanding the concept of human resource management which is used to develop the professional skills of teachers or educators in Islamic educational institutions, especially in institutions called Islamic boarding schools. The research stage that the author carried out was a teaching practicum which was then narrated in the form of descriptions and narrative data. The research used in this treatise is qualitative research by conducting interviews with PKM Madrasah Diniyyah Curriculum who play a role in delegating, supervising and evaluating teacher performance. The results of the research are: basic concepts of HR management as teacher or educator facilitators, evaluation of teacher activity and revitalization and empowerment of students who have graduated from Diniyyah.